Pengaruh E-Service Quality, Promosi Dan Harga Terhadap Minat Beli Pada E-Commerce Shopee Saat Pandemi Covid-19 Di Kota Banjarmasin - Tumbio, Rehardi Gemilang; Hairudin, Hairudin (Universitas Lambung Mangkurat, 2023)
The purpose of this study was to determine the effect of E-Service Quality, Promotion and Price on Buying Interest at E-Commerce Shopee during the Covid-19 pandemic in Banjarmasin City. This study uses a quantitative approach in the form of explanatory. The sample used in this study amounted to 40 respondents. The sampling technique used in this research is purposive sampling.The results based on the partial test (t test) show that E-Service Quality (X1), Promotion (X2) and Price (X3) have a partial and significant effect on Purchase Interest (Y) with each effect of 25.5%, 23.9% and 30.9%. Meanwhile, based on the simultaneous test (f test) E-Service Quality (X1), Promotion (X2) and Price (X3) have a simultaneous and significant effect on Purchase Interest (Y) with an effect of 64.5% while 35.5% is the influence of other variables not examined in this study Keywords: E-service quality, promotion, price and buying interest